Intracranial desmoid tumor simulating a trigeminal schwannoma: case report and literature review - Beatrice Silva Fernandes; Jessica Fernandes Vasconcelos; Paulo Eduardo Goncalves; Joilson Francisco de Souza Junior; Ricardo Queiroz Gurgel; Arthur Maynart Pereira Oliveira (Egyptian Journal of Neurosurgery)
Abstract Background Desmoid tumor (DT) is a non-encapsulated and locally aggressive benign neoplasm. Although it does not have malignant behavior, it has a high capacity for local growth. Intracranial DTs are extremely rare and constitute a major diagnostic and therapeutic challenge. In these cases, neurosurgical intervention is the best option and should be performed early; however, it is still little discussed in the literature. Case presentation We report the case of a 50-year-old male patient, complaining of pain in the region of the right ear and discomfort in the region of the maxilla on the same side for 5 months. Contrast-enhanced magnetic resonance image (MRI) of the skull base and face showed a homogeneous contrast uptake lesion in the region of Meckel’s cave extending inferiorly to the infratemporal fossa with an intracranial and extracranial portion. The patient underwent partial resection of the lesion. The anatomopathological examination showed an infiltrative fibroproliferative lesion (“desmoid-like”), and immunohistochemistry showed myofibroblastic differentiation leading to the possibility of DT. Despite two attempts, the difficult related to skull base location and local invasiveness and the sarcomatous transformation our patient evolved with death 23 months after the diagnosis. Conclusions Intracranial DT is a rare and difficult-to-control condition, because despite being considered benign, its infiltrative nature becomes a challenge in neurosurgical management. Neurosurgery has a positive impact on the quality of life of these patients, considering the improvement of symptoms and the possibility of making a more appropriate diagnosis.